Serum lipid profile in non-polycystic ovary syndrome and polycystic ovary syndrome women: a comparative and correlational study - Halasawadekar, Nimish R.; Ramanand, Jaiprakash B.; Ramanand, Sunita J.; Raparti, Girish T.; Patil, Praveenkumar T.; Shah, Ruchi D.; Kumbhar, Arvind V. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Polycystic ovary syndrome (PCOS), in addition to impaired ovulation, also affects metabolic pathways. Dyslipidemia, occurring in PCOS women leads to cardiovascular diseases in them. The purpose of the present study was to compare lipid profile and its correlation with biochemical and hormonal parameters in PCOS and non PCOS women, to analyse the correlation of lipid profile with hirsutism and body mass index (BMI) in PCOS women. Methods: The present study includes 68 women divided into non PCOS groups (n=30) and PCOS (n=38) as defined by Rotterdam criteria. PCOS group further divided into overweight / obese (n=23) and normal weight subgroups (n=15). Lipid profile, fasting blood glucose and hormonal profile were done in all the groups. Results: TG and TC/HDL ratio were significantly high in PCOS group. Hirsute patients had raised LDL levels as compared to non-hirsute. LDL showed positive significant correlation with insulin, HOMA, testosterone in PCOS group. TC was significantly positively correlated with insulin and HOMA in PCOS group. In both normal weight and overweight / obese PCOS subgroups, LDL had positive and significant correlation with testosterone. TC showed positive and significant correlation with HOMA in overweight/obese subgroup. HDL showed positive and highly significant correlation with FSH in normal weight PCOS. Conclusions: Hyperandrogenism in PCOS may be additionally marked by raised LDL. Overweight/obese PCOS subgroup may be prone to dyslipidemia as well as deranged glucose homeostasis, thereby making it an important therapeutic target.